2019
DOI: 10.1002/ecy.2688
|View full text |Cite
|
Sign up to set email alerts
|

Invasive earthworm and soil litter response to the experimental removal of white‐tailed deer and an invasive shrub

Abstract: Recent studies have shown that complex species interactions can regulate above‐ and belowground processes in terrestrial systems. Ungulate herbivory and invasive species are known to have strong effects on plant communities in some systems, but their impacts on soil biota and belowground processes are lesser known. Growing evidence suggests white‐tailed deer (Odocoileus virginianus) and invasive plants facilitate increased abundance of exotic earthworms in temperate forests of the eastern United States. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
1
8
1
Order By: Relevance
“…Note that in differentiating the two models (inclusion vs. subtraction), we use the term subtraction as opposed to exclusion to avoid confusing the approach with methods that involve the physical removal of invasive plants from field plots (Tekiela and Barney 2017) and/or the experimental exclusion of invasive animals and plants (Stokeld et al 2018, Mahon and Crist 2019). Further, for brevity, we also use the phrase “the two assemblage models” when discussing the inclusion and subtraction models in unison.…”
Section: Methodsmentioning
confidence: 99%
“…Note that in differentiating the two models (inclusion vs. subtraction), we use the term subtraction as opposed to exclusion to avoid confusing the approach with methods that involve the physical removal of invasive plants from field plots (Tekiela and Barney 2017) and/or the experimental exclusion of invasive animals and plants (Stokeld et al 2018, Mahon and Crist 2019). Further, for brevity, we also use the phrase “the two assemblage models” when discussing the inclusion and subtraction models in unison.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, our understanding of how to control invasive earthworms within natural areas remains limited (Chang et al, 2021; Frelich et al, 2019). However, strong correlational evidence suggests that earthworms decline following fencing to exclude deer in northeastern forests (Dávalos, Simpson, et al, 2015; Mahon & Crist, 2019). Fencing to exclude deer may therefore be beneficial, especially as we also found that fencing decreased V. rossicum as well as A. petiolata , another common plant invader.…”
Section: Discussionmentioning
confidence: 99%
“…In North America, greater earthworm abundance and diversity are also associated with lower plant diversity and more graminoids (Craven et al, 2017). Additionally, earthworms alter competitive outcomes of interactions between native and invasive species (Nuzzo et al, 2009; Whitfeld et al, 2014) and may become more abundant in the presence of deer (Dávalos, Simpson, et al, 2015; Mahon & Crist, 2019). Invasive plants, earthworms, and white‐tailed deer may therefore interact with each other (Dávalos et al, 2014; Fisichelli & Miller, 2018) to drive plant community change in forests in the northeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on a few pathways, but acknowledge that other direct and indirect effects of large herbivores on the target forb species may be operating in our study system. These may include direct negative effects such as trampling (Schrama et al, 2013;van der Wal & Brooker, 2004), and indirect effects such as the deposition of animal excreta (Augustine & McNaughton, 2006;Day & Detling, 1990;Frank et al, 2018;Wang et al, 2018), the influences on insect herbivores (Huntzinger et al, 2008;Rambo & Faeth, 1999;van Klink et al, 2015;Zhong et al, 2017), pollinators (Guy et al, 2021;V azquez & Simberloff, 2004), seed and seedling predators (Foster et al, 2014;Goheen et al, 2010;Maclean et al, 2011), and decomposers (Eldridge et al, 2017;Mahon & Crist, 2019;Sankaran & Augustine, 2004). Further investigations are needed to assess the relative importance of these lessstudied indirect factors in mediating plant population and communities (see Figure 6).…”
Section: Discussionmentioning
confidence: 99%